Effects of the Mediterranean Diet on Cardiovascular Outcomes-A Systematic Review and Meta-Analysis. - Thaminda Liyanage; Toshiharu Ninomiya; Amanda Wang; Amanda Wang; Bruce Neal; Min Jun; Muh Geot Wong; Meg Jardine; Graham S Hillis; Vlado Perkovic (PLoS ONE)
Background A Mediterranean dietary pattern is widely recommended for the prevention of chronic disease. We sought to define the most likely effects of the Mediterranean diet on vascular disease and mortality. Methods We searched MEDLINE, EMBASE and the Cochrane Central Register without language restriction for randomized controlled trials comparing Mediterranean to control diets. Data on study design, patient characteristics, interventions, follow-up duration, outcomes and adverse events were sought. Individual study relative risks (RR) were pooled to create summary estimates. Results Six studies with a total of 10950 participants were included. Effects on major vascular events (n = 477), death (n = 693) and vascular deaths (n = 315) were reported for 3, 5 and 4 studies respectively. For one large study (n = 1000) there were serious concerns about the integrity of the data. When data for all studies were combined there was evidence of protection against major vascular events (RR 0.63, 95% confidence interval 0.53-0.75), coronary events (0.65, 0.50-0.85), stroke (0.65, 0.48-0.88) and heart failure (0.30, 0.17-0.56) but not for all-cause mortality (1.00, 0.86-1.15) or cardiovascular mortality (0.90, 0.72-1.11). After the study of concern was excluded the benefit for vascular events (0.69, 0.55-0.86) and stroke (0.66, 0.48-0.92) persisted but apparently positive findings for coronary events (0.73, 0.51-1.05) and heart failure (0.25, 0.05-1.17) disappeared. Conclusion The Mediterranean diet may protect against vascular disease. However, both the quantity and quality of the available evidence is limited and highly variable. Results must be interpreted with caution.